Greater than Equal : African American Struggles for Schools and Citizenship in North Carolina, 1919-1965 - Thuesen, Sarah Caroline (Book collections on Project MUSE., 2013)
During the half century preceding widespread school integration, Black North Carolinians engaged in a dramatic struggle for equal educational opportunity as segregated schooling flourished. Drawing on archival records and oral histories, this book gives voice to students, parents, teachers, school officials, and civic leaders to reconstruct this high-stakes drama. It explores how African Americans pressed for equality in curricula, higher education, teacher salaries, and school facilities; how white officials co-opted equalization as a means of forestalling integration; and, finally, how Black activism for equality evolved into a fight for something "greater than equal" - integrated schools that served as models of civic inclusion.